Chapter Giudizi universali. Reti devozionali e tensioni escatologiche attorno ai gesuati milanesi - Rossetti, Edoardo (Fragmentaria. Studi di storia culturale e antropologia religiosa, 2020)
This essay provides an outline of the familial, social, and cultural network of the Milanese Jesuati between the end of the fifteenth century and the first decades of the sixteenth century. Particular attention is given to their interactions with Cardinal Bernardino López de Carvajal, one of the protagonists of the schismatic Council of Pisa-Milan (1510-1512). Starting from the creation of their settlement of San Girolamo, new documentary evidence is employed to show how the surrounding urban area and the physical buildings that should have been erected there actually mirrored the local network of both the Jesuati and Carvajal. The patronage of the cardinal in San Girolamo and the creation of a Last Judgement fresco are then discussed and connected to the eschatological tensions stirring Milan at the time.